Rancangan Simulasi Sistem Dinamis Proyeksi Pertumbuhan Penduduk dan Penyusutan Lahan Sawah Terhadap Produksi Pangan di Kabupaten Bantul - Lolanda Hamim Annisa; Pala, Asmarantara (LP3M Universitas Putra Bangsa, 2024)
Population growth that is not balanced with the availability of agricultural land can result in shrinkage of rice fields, threatening food security and the sustainability of the agricultural sector in the region. The method used in this research is a simulation modeling method with a dynamic system approach. The simulation model was developed based on study data on population growth and reduction in forest area, as well as other factors that could influence it. Dynamic systems techniques are often used to analyze systems that have many dependencies between components. This loop shows how changes in a system element affect future changes in the same element through a series of cause and effect relationships. The increasing need for land triggers a reduction in the area of rice fields, which results in a decrease in food production. Population growth in Bantul district has resulted in the need for land, where the depreciation of rice fields has increased, resulting in a decrease in the amount of food production in the area. Projected population growth for Bantul Regency shows an increase of 10% per year, which can provide an idea of the burden faced by this region in providing services and infrastructure for its growing population. The analysis shows that there is a significant relationship between population growth and shrinkage of rice fields. The increasing need for food due to rapid population growth can put significant pressure on food security at the local level.